Information System for Monitoring the Development of Children With Special Needs - Andryanto Aman; Listia Utami; Muhammad Khaidir Alif Aras; Mauli Kasmi (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2022)
Supervision of students is mostly only carried out by the school. Some parents have a busy schedule so they monitor their children's development at school. Information about the development of the student learning process is usually only received by parents once a semester, namely when receiving the report card, this is what makes SLB C YPPLB 2 Makassar need a monitoring system in providing information to schools and parents of students. The purpose of this study is to build an information system for monitoring the development of children with special needs at SLB C YPPLB 2 Makasar City which will make it easier for parents to directly monitor their child's development. These data were obtained through 1) Observation, 2) Interviews, and 3) Documentation. By using the BlackBox system testing methods in the manufacture of this application. In making this application the application design methods include: Needs Analysis, Design and Software, Implementation and Unit Testing, System Integration / Testing, and System Maintenance. The results of this study showed that the development monitoring system for children with special needs at SLB C YPPLB 2 Makassar City was declared suitable for use with percentage results on testing aspects with a percentage rate of 90% which received a good response.